2010
DOI: 10.1016/j.jpain.2009.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Method to Quantify Histochemical Changes Throughout the Mediolateral Axis of the Substantia Gelatinosa After Spared Nerve Injury: Characterization with TRPV1 and Substance P

Abstract: Nerve injury dramatically increases or decreases protein expression in the spinal cord dorsal horn. Whether the spatial distribution of these changes is restricted to the central innervation territories of injured nerves or could spread to adjacent territories in the dorsal horn is not understood. To address this question, we developed a simple computer software-assisted method to precisely distinguish and efficiently quantify immunohistochemical staining patterns across the mediolateral axis of the dorsal hor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 37 publications
2
22
0
1
Order By: Relevance
“…These results are consistent with a report that SNI did not reduce the expression of TRPV1 immunoreactivity within the territory innervated by the uninjured sural nerve in the spinal dorsal horn (31). From these results, it is considered that normal thermal sensitivity was maintained because of sparing of TRPV1-positive fibers in this SNI model.…”
Section: Discussionsupporting
confidence: 92%
“…These results are consistent with a report that SNI did not reduce the expression of TRPV1 immunoreactivity within the territory innervated by the uninjured sural nerve in the spinal dorsal horn (31). From these results, it is considered that normal thermal sensitivity was maintained because of sparing of TRPV1-positive fibers in this SNI model.…”
Section: Discussionsupporting
confidence: 92%
“…Investigations of nerve injury-induced activation of astrocytes in areas of the dorsal horn innervated by injured versus uninjured afferents are sparse [4;15;94]. Here, our immunohistochemical quantification method [15] revealed that nerve injury increased GFAP expression in regions of the ipsilateral dorsal horn innervated by both injured tibial afferents (medial) and uninjured sural afferents (lateral).…”
Section: Discussionmentioning
confidence: 94%
“…Here, our immunohistochemical quantification method [15] revealed that nerve injury increased GFAP expression in regions of the ipsilateral dorsal horn innervated by both injured tibial afferents (medial) and uninjured sural afferents (lateral). This is consistent with qualitative studies showing that astrocyte activation extends beyond injured territories [4], and suggests that astrocytes induce hyperalgesia by sensitizing intact nociceptive pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We focused our quantification of the number of pERK immunopositive cell profiles within lamina I-II, where the majority of C-fibers and nociceptive peripheral afferents terminate within the dorsal horn 4, 14 . Colabeling of pERK with NeuN is expressed as the percentage of the total number of pERK profiles in laminae I-II also expressing NeuN.…”
Section: Methodsmentioning
confidence: 99%